Social and health care enterprise architecture maturity assessment: towards a more efficient steering - Vuokko, Riikka; Palojoki, Sari (Finnish Journal of eHealth and eWelfare, 2021)
In the social and health care sector, results of enterprise architecture (EA) have not been extensively assessed even though the method has been utilized for almost two decades. The aim of the study is to examine and compare some of the key maturity models and their application of EA. Based on the literature, the study was grounded on the assumption that increasing the maturity of the EA benefits steering of the public administration. The method of the narrative literature review was applied. The study produced a comparison of maturity assessment models EAMM, DyAMM, MIT CISR, and SAMM. Additionally, the evaluation components of DyAMM and SAMM were examined. Results indicate that the maturity assessment of EA has been examined to a small extent. The weakness of the theoretical foundation challenges the EA development and its maturity assessment. The dimensions identified in the theoretical models could be applied more widely in order to make more effective use of the EA in its role of the steering support in public administration. The development of maturity assessment models requires further research, in which the theoretical examination is accompanied by testing the model with real data. In this way, models can be developed evidence-based and not just on the terms of individual projects. By these means, the models would provide a reliable and target-specific assessment to improve steering in public administration.